2019
DOI: 10.1111/hepr.13365
|View full text |Cite
|
Sign up to set email alerts
|

Malic enzyme 1 is a potential marker of combined hepatocellular cholangiocarcinoma, subtype with stem‐cell features, intermediate‐cell type

Abstract: Aim Combined hepatocellular cholangiocarcinoma, subtype with stem‐cell features, intermediate‐cell subtype (INT) shows various histological appearances and could be misdiagnosed as intrahepatic cholangiocarcinoma (iCCA). In the present study, we aimed to identify specific histological diagnostic markers of INT. Methods We extracted RNA from FFPE sections of six INT, five iCCA, and five hepatocellular carcinoma (HCC) cases and compared gene expression between INT, iCCA, and HCC by microarray analysis. We then u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Consistent with a previous study, we found that FMO3 suppresses tumor progression by decreasing cell viability, hence it is a protective index [23]. In addition, our analysis revealed that ME1 or ZIC2, which exhibit stem-cell features, correlated with poor prognosis, hence are risk indexes [24,25]. However, these previous studies reported the presence of potential errors and bias in their analyses.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with a previous study, we found that FMO3 suppresses tumor progression by decreasing cell viability, hence it is a protective index [23]. In addition, our analysis revealed that ME1 or ZIC2, which exhibit stem-cell features, correlated with poor prognosis, hence are risk indexes [24,25]. However, these previous studies reported the presence of potential errors and bias in their analyses.…”
Section: Discussionsupporting
confidence: 90%
“…Because most of the cases collected in this study were smaller than 5cm in diameter, and cHCC-CC contained both hepatocellular carcinoma and cholangiocarcinoma, there was no significant difference in AFP, HBsAg and HBeAg between them. Most scholars believe that it originated from hepatic progenitor cells though there are different opinions on the origin of cHCC-CC [26] [27].Hepatic progenitor cells are a group of undifferentiated cells with hepatocyte function in normal human liver, which are mainly distributed in the Hering duct of portal vein and bile canaliculi [28].On the other hand, the Hering duct constructs the relationship between the biliary system and the intralobular anatomy and microscopic system of the liver. Once cHCC-CC occurs, it is easy to have multiple lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Cytoplasmic-localized malic enzyme 1 (ME1) reversibly catalyzes the NADP + -dependent conversion of malate to pyruvate (Chen et al, 2019b;Jiang et al, 2013;Lu et al, 2018). ME1 is overexpressed in a variety of cancers and promotes the growth of CRC as well as gastric, breast, and liver cancers (Liao et al, 2018;Lu et al, 2018;Mihara et al, 2019;Nakashima et al, 2018). ME1 plays a critical role in the development of spontaneous and azoxymethane (AOM)/dextran sodium sulphate (DSS)-induced CRCs in mice (Fernandes et al, 2018;Shen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%